“WOMEN'S VOICE” IN LITERATURE: THE DISTINCTIVE POETICS OF MAYA ANGELOU AND TONI MORRISON - Tursunova Mohira Ilxomjanovna (Western European Studies, 2025)
This article explores the literary interpretation of the concept of the “female voice” in the works of African American writers Maya Angelou and Toni Morrison. Their works center on themes such as the role of Black women in society, identity, memory, and the reclamation of a silenced voice. In Angelou’s poetry, the inner strength of womanhood is revealed through personal experience and lyrical expression, while in Morrison’s novels, the voice of the Black woman is restored through historical trauma and collective memory. The study presents a comparative analysis of the two authors’ literary styles, drawing on feminist literary criticism, racial theory, and poetic-stylistic approaches
Keywords: female voice; African American literature; Maya Angelou